Konstruksi Ring Bersih dari Sebarang Ring - Kartika Sari; Indah Emilia Wijayanti (Jurnal Matematika, 2015)
The aims of this research was to construct a clean ring from any ring.  The base on the fact  that the endomorphism ring of every pure-injective module is clean, it was constructed a clean ring from any ring. So, the result of this research was it always could be constructed a clean ring from any ring.